Computational component analysis techniques for high temperature power plant applications - Rouse, James Paul (2014)
There is a trend in the power industry for high temperature components (such as steam pipe work) to be operated in an increasingly arduous fashion. This would involve the use of elevated steam temperatures/pressures and a greater frequency of start up/shut down cycles. Such generation strategies are being adopted due to the need for thermally efficient power supply that can match fluctuating market demands. If these generation strategies are to be implemented safely it is critical that careful analysis of the system components is conducted in order to ensure that premature failure does not occur. The advanced material models and techniques that are used in academia to simulate these components are often out of reach of the engineers working in industry.